Opinions de femmes sure les facteurs de leur réinsertion professionelle - Bernard, Carmen; Dupont, Pierrette; Gingras, Marcelle (Canadian Journal of Counselling and Psychotherapy, 2007)
This article presents the results of an exploratory research project undertaken with women from 30 to 50 years of age, who participated in a program aimed at facilitating their integration into the work force. The goal of this study was to identify factors that could influence the stage of their career development that has been called professional reinsertion. The gathering of the data was accomplished by means of semi-structured interviews and with the help of a questionnaire that was half-open and half-closed. The results of the respondents reveal certain factors that played an important role in each of the three phases of the process of professional reinsertion, that is, in their decision to return to the work force, in the career choice that they made, and in the course of their integration as employees. Certain implications are drawn for the practice of career counselling, while taking into account the limits of the study.